CFD Simulations of Turbulent Flows in a Twin Swirl Combustor by RANS and Hybrid RANS/LES Methods. (2015) - Liu, Yinli; Tang, Hao; Tian, Zhaofeng; Zheng, Haifei
Abstract: A confined isothermal flow in a Twin Swirl Combustor (TSC) was studied under both steady and transient conditions. The Reynolds Averaged Navier-Stokes (RANS) simulation was carried out to investigate the time-averaged flow features in TSC under different ratios of the primary air flow rate to the secondary air flow rate. The steady-state velocity profiles inside the combustion chamber were analyzed using both Renormalized Group (RNG) k-ɛ model and Shear Stress Transport (SST) turbulence model. For the transient conditions, the Scale Adaptive Simulation (SAS) method based on the SST model was used to probe the instantaneous three dimensional (3D) vortex structures to better understand the formation of the internal recirculation zone (IRZ). The existence of a pressing vortex cores (PVC) and a hurricane-shaped vortical structure in the TSC were captured by the SAS model. The SAS model can yield vortex-level results similar to large eddy simulation (LES) prediction while saves much more computational resource. This paper briefly reports some preliminary results of this study.